Factors Associated With Late Prematurity in the University Hospital of Valle Cali, Colombia During 2013-2014 - Javier Torres-Muñoz; Carlos Alberto Jiménez-Fernandez; Rubi Rocio Ortega; Darly Janeth Marin Cuero; Diana Marcela Mendoza (Frontiers Media S.A., 2020)
Introduction: The birth rate of late premature babies has been increasing in recent years, composing now 75% of all premature births. This growing trend can be explained by different demographic transformations such as an increase in the demand for infertility treatments, older maternal age and the higher incidence of multiple pregnancies, cesarean sections, and labor induction. These premature babies contribute 30% to the global neonatal mortality rate.Objective: To identify the factors associated with late prematurity at the Hospital Universitario del Valle during the years 2013-2014.Methodology: Case and control design, 424 patients, 212 cases and 212 controls participated. Cases were defined as newborns with gestational age between 34 and 36 weeks and 6 days old. For the analysis, logistic regression models were developed and association forces (OR) were determined.Results: A univariate analysis shows that the proportion of teenage pregnant women corresponds to 22.64%. Bivariate analysis shows the maternal morbidity due to hypertensive disorders was 1.6 times higher (95% CI 1.06-2.63), the obstetric alterations in 2.9 times (CI of 95% 1.56-5.44), late preterm infants require more oxygen support 3.26 times (95% CI 1.76-6.03). After adjusting the model, it was found that late premature infants have a 3-fold probability of requiring some resuscitation maneuver (ORa 3.23 95% CI 2.09-4.99), birth is higher by cesarean section by 4.17 times (ORa 4.17 IC 95% 2.50-6.98), maternal morbidity was higher in 1.37 times (ORa 1.37 95% CI 1.14-1.65). The morbidity of the newborn was greater, close to the statistical significance for late premature infants in 1.26 times (ORa 1.26 95% CI 0.97-1.64).Conclusions: Late premature births in this study show a higher probability of developing morbidity, have a greater opportunity to be born by cesarean section, are products of mothers with morbidity (specifically hypertensive disorders), and require further resuscitation with a need of early obstetric intervention.